Calycosin as a Novel PI3K Activator Reduces Inflammation and Fibrosis in Heart Failure Through AKT–IKK/STAT3 Axis - Wang, Xiaoping; Li, Weili; Zhang, Yawen; Sun, Qianbin; Cao, Jing; Tan, NanNan; Yang, Shuangjie; Lu, Linghui; Zhang, Qian; Wei, Peng; Ma, Xiao; Wang, Wei; et al. (Frontiers in Pharmacology, 2022)
Aim: Inflammation and fibrosis have been shown to be critical factors in heart failure (HF) progression. Calycosin (Cal) is the major active component of Astragalus mongholicus Bunge and has been reported to have therapeutic effects on the cardiac dysfunction after myocardial infarction. However, whether Cal could ameliorate myocardial infarction (MI)-induced inflammation and fibrosis and precise mechanisms remain uncertain. The aim of this study is to explore the role of Cal in HF and to clarify the underlying mechanisms. Methods: For in vivo experiments, rats underwent left anterior descending (LAD) artery ligation for HF model, and the cardioprotective effects of Cal were measured by echocardiographic assessment and histological examination. RNA-seq approach was applied to explore potential differential genes and pathways. For further mechanistic study, pro-inflammatory conditioned media (CM)-induced H9C2 cells injury model and TGFβ-stimulated cardiac fibroblasts model were applied to determine the regulatory mechanisms of Cal. Results: In vivo experiment, echocardiography results showed that Cal significantly improved heart function. GO and Reactome enrichment revealed that inflammation and fibrosis pathway are involved in Cal-treated group. KEGG enrichment indicated that PI3K-AKT pathway is enriched in the Cal-treated group. Further experiments proved that Cal alleviated cardiomyocyte inflammatory responses evidenced by down-regulating the expressions of phosphorylated IκB kinase α/β (p-IKKα/β), phosphorylated nuclear factor kapa B (p-NFκB) and tumor necrosis factor α (TNFα). Besides, Cal effectively attenuated cardiac fibrosis through the inhibitions of expressions and depositions of collagen I and collagen III. In vitro experiments, the phosphatidylinositol 3 kinase (PI3K) inhibitor LY294002 could abrogate the anti-inflammation and anti-fibrosis therapeutic effects of Cal, demonstrating that the cardio-protective effects of Cal were mediated through upregulations of PI3K and serine/threonine kinase (AKT). Conclusion: Cal inhibited inflammation and fibrosis via activation of the PI3K-AKT pathway in H9C2 cells, fibroblasts, and heart failure post-acute myocardial infarction rats.